Horse riding – related injuries from the point of view of a neurosurgeon - Siedlecki, Zygmunt; Szafrańska, Małgorzata; Główczewska-Siedlecka, Emilia; Śniegocki, Maciej (Journal of Education, Health and Sport, 2022)
Horse riding (equestrianism) is a very old form of physical activity, and today it has become a very popular sport and recreation. Similarly to other sports, equestrianism carries potential risk of injuries, most often caused by a fall from a horse back. Horse riding can cause spine and brain injuries, which are treated by neurosurgeons. Both brain and spine injuries can potentially be life - threatening or cause severe disability. In our neurosurgical center, horse - related injuries accounted for 7.69% of all sports - related injuries. We treated 4 girls in total: 3 with spinal injuries, 1 with brain injuries. Girls with spine injuries were treated conservatively, and girls with brain injuries - surgically. All patients had good prognosis. We have reviewed the literature about horse - related trauma. Literature showed that they occurred more often in young age patients and mainly in girls, which was consistent with our observations. Numerous authors emphasized the protecting role helmets. The authors emphasized the key role of education and proper care of coach. Although the literature described some fatal horse - related injuries, in our material all patients were healed and returned to a perfect clinical state.